Adrenal Cavernous Hemangioma: A Case Report with Review of the Literature - Noh, Joseph Joonho; Choi, Sung Hoon; Hwang, Ho Kyoung; Kang, Chang Moo; Lee, Woo Jung (JOP. Journal of the Pancreas, 2014)
Context Adrenal cavernous hemangioma is a rare type of tumor that is usually diagnosed post-operatively. There have only been approximately 63 cases reported in the literature to date. Case report We report a case of adrenal cavernous hemangioma in a 27-year-old pregnant woman. The mass was discovered on ultrasonography when she visited a gastroenterologist for vague epigastric discomfort and vomiting. The laboratory tests were within normal limits and did not show any features suggestive of adrenal endocrinologic dysfunction. Computed Tomography (CT) revealed a well-defined 7.8 × 7.8 oval mass in the right adrenal gland with speckled calcifications. The mass was removed by transabdominal laparoscopic surgery. Strong positive immunostaining for CD31 and CD34 with weakly positive staining for podoplanin/D2-40 confirmed the diagnosis of cavernous hemangioma. Conclusions We reviewed 52 case reports of adrenal cavernous hemangioma in an attempt to identify tumor characteristics. More than half of the patients reviewed showed a heterogeneous internal structure of the mass with peripheral patchy enhancement on CT. They also showed focal or speckled calcifications either on X-ray or CT. Nevertheless, many of these characteristics overlap with the imaging phenotypes of other common diseases of the adrenal gland and therefore do not seem to provide definite evidence for differential diagnosis. Laparoscopic approach is a feasible and safe modality to remove adrenal cavernous hemangiomas because they seem to form a rigid fibrotic capsule; hence the risk of bleeding due to surgical manipulation is relatively low. Image: Round and encapsulated fibrotic tumor.